A FUTURE APPROACHES, SOCIAL ORGANIZATION AND THEIR ECONOMIC CONSEQUENCES OF THE INFORMATIONAL SOCIETY – KNOWLEDGE SOCIETY - NICULAE DAVIDESCU; DELIA BABEANU (Challenges of the Knowledge Society)
The paper is the result of scientific study under doctoral thesis “Information Society and its Economic Effects” and contains seven sections: -section 1: “Globalization, Development and Information Society”; -section 2: “The Impact of the “Digital Divide” and “Digital Inequality” Phenomena” ; -section 3: “Information Society –Knowledge Society, Definition, Objectives and Strategies” ; -section 4: “Social Structures and New Life Patterns in Information Society” ; -section 5: “Virtual Organizations, Activities and Businesses” ; -section 6: “Strategies, Programmes and Courses of the Information Society Approach” ; -section 7: “The Economic Effects Foreseeable through the Implementation of Information Society–Knowledge Society”.